Existence of State Administrative Court in Resolving Disputes - Diantika Chayani (JUSTICES: Journal of Law, 2023)
In Indonesia, PTUN is part of the judiciary which is organizationally under the Supreme Court and does not stand alone as in countries which base their legal system on codified civil law in general, because it is under the Supreme Court, hence judicial technical development. The State Administrative Court is an institution that has an important role in protecting the rights of people who are harmed by the enactment of a State Administrative Decree (KTUN) made by government officials. In addition, the PTUN's authority in assessing the actions of government officials can be used as a control or supervision of government officials. Law No. 5 of 1986 concerning State Administrative Radiation in Article 47 it is emphasized that the State Administrative Court has the duty and authority to examine, decide and resolve State Administrative disputes (PTUN).